Efektivitas Perlindungan Konsumen dalam Ekosistem E-Commerce melalui Pendekatan Hukum Empiris - Ahmad Ramadhan; Dewi Lestari (Universitas Sains dan Teknologi Komputer, 2025)
The rapid expansion of Indonesia’s digital economy has significantly transformed consumer behavior, accompanied by a sharp increase in e-commerce transactions that reached IDR 602 trillion in 2023. However, this economic growth has also led to a notable rise in consumer rights violations, creating an urgent need to evaluate the effectiveness of existing legal protections. This study aims to analyze the effectiveness of Indonesian consumer protection regulations, particularly the Consumer Protection Law, the Electronic Information and Transactions Law (ITE Law), and Government Regulation No. 80 of 2019 on Electronic Commerce, in addressing digital consumer disputes. Using an empirical legal research design with a qualitative descriptive approach, data were collected through in-depth interviews with 10 consumers, 6 business actors, and 3 officials from the Consumer Dispute Settlement Agency (BPSK), supported by document analysis and digital observation. The findings indicate that 38 percent of reported violations involve nonconforming goods, 25 percent involve failed refunds, and 20 percent relate to the misuse of personal data. These results reveal that regulatory implementation remains fragmented, with limited institutional coordination and insufficient integration of digital mechanisms. The study contributes to understanding how legal systems adapt to digital economic dynamics by highlighting the interaction between regulation, technology, and institutional capacity. The novelty of this research lies in its empirical examination of the adaptability of Indonesia’s legal framework to digital transaction environments, offering theoretical insights and practical implications for strengthening technology-based consumer protection.